Getting Started With Open Badges and Open Microcredentials - Clements, Kyle; West, Richard Edward; Hunsaker, Enoch (International Review of Research in Open and Distributed Learning, 2020)
This article is intended as a practical resource to help interested organizations design and implement an open badging system. Open badges are a type of open credential designed to recognize a variety of skills, knowledge, and experiences, both inside and outside of traditional educational settings. While growing in popularity, common questions asked by those interested in using open badges include: How do I get started? What technologies exist to produce open badges? And what do I need to know? This article seeks to address questions such as these. First, we introduce the reader to key terms in the badging world and explore open badge design precedents, responding to who, what, how, where, and why open badges have been used in the past. Drawing on this research as well as our own personal experience, we then present a possible framework for getting started with open badges and a step-by-step guide for implementing that framework within your organization.